2021
DOI: 10.2478/fhort-2021-0027
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of postharvest storability of Ponkan mandarins stored at different temperatures

Abstract: The effects of storage temperature on postharvest storability, quality attributes and antioxidant enzyme activities of harvested Ponkan mandarins were investigated. Fresh fruits were randomly divided into four groups and stored at different temperatures [5 ± 1 °C (S5), 10 ± 1 °C (S10), 15 ± 1 °C (S15), and 20 ± 1 °C (S20 or control)] for 120 days. The results indicated that, compared with the control fruit, low-temperature storage at 10 °C significantly delayed the increase in fruit decay rate, weight loss, ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The content of phenolics in the cherry fruit showed a decreasing trend during storage at 2 °C for 21 days . Comparing the effects of storage temperature (5, 10, 15, and 20 °C) on phenolic compounds of Ponkan mandarins, it was found that the total phenol and total flavonoid were greatly retained at 10 °C . After storage of an aronia berry for 12 weeks at 4 °C, anthocyanins decreased by 36% and the total phenolics decreased by 21%, but frozen storage (−20 °C) increased the polyphenol content for the first six months and then decreased .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The content of phenolics in the cherry fruit showed a decreasing trend during storage at 2 °C for 21 days . Comparing the effects of storage temperature (5, 10, 15, and 20 °C) on phenolic compounds of Ponkan mandarins, it was found that the total phenol and total flavonoid were greatly retained at 10 °C . After storage of an aronia berry for 12 weeks at 4 °C, anthocyanins decreased by 36% and the total phenolics decreased by 21%, but frozen storage (−20 °C) increased the polyphenol content for the first six months and then decreased .…”
Section: Discussionmentioning
confidence: 98%
“…15 Comparing the effects of storage temperature (5, 10, 15, and 20 °C) on phenolic compounds of Ponkan mandarins, it was found that the total phenol and total flavonoid were greatly retained at 10 °C. 47 After storage of an aronia berry for 12 weeks at 4 °C, anthocyanins decreased by 36% and the total phenolics decreased by 21%, but frozen storage (−20 °C) increased the polyphenol content for the first six months and then decreased. 48 The polyphenol content showed a trend of first increasing and then decreasing during storage, which may be because of the fact that free polyphenols are more sensitive to light, temperature, and other enzymes, resulting in different total phenol contents at different temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that higher temperatures, such as 7.5 °C, enhance color development compared to lower temperatures, like 0.5 °C. This could be attributed to the fact that at higher temperatures, chlorophyll degradation is accelerated, allowing the orange color to become more pronounced [ 32 , 40 , 42 , 45 , 46 ]. However, it is worth noting that GA 3 -treated fruits still exhibited a lower color index compared to the other treatments and the control.…”
Section: Discussionmentioning
confidence: 99%